The Effect of Self-Efficacy, Self-Leadership, and Work Ethic on Employee Performance in Manufacturing Companies - Mujanah, Siti; Utami, Citra (KnE Social Sciences, 2023)
The purpose of this research was to analyze the role of self-leadership, self-efficacy, and work ethic on employee performance in manufacturing companies in Indonesia. This study used a quantitative approach with explanatory methods to determine the causality among variables. The population was manufacturing employees in Surabaya, Indonesia, with a sample of 260 employees who responded to the questionnaire distributed via Google Forms. Data analysis was done using multiple linear regression. T-test and F-test were used to test the hypothesis. The results showed that selfleadership, self-efficacy and work ethic play a role in the value of 0.680. In other words, the three aspects had a 68% influence on improving employee performance. While the hypothesis testing showed, the F-test had a significant effect of <0.05. The results implied a significant effect, but only self-efficacy has a significant effect on employee performance. In contrast, self-leadership and work ethic have no significant effect. This indicates that employees should be encouraged to have self-efficacy to improve their performance. Keywords: Self-Efficacy, Self-Leadership, work ethic and employee performance